PENGARUH KOMPENSASI, LEVERAGE, UKURAN PERUSAHAAN, EARNINGS POWER TERHADAP MANAJEMEN LABA - Santhi Yuliana Sosiawan (Fakultas Bisnis UKDW, 2012)
According to agency theory there are separation of fucntion between principal and agent. This separation of function creates different interest between parties that lead to a discretionof the manager to maximize the earnings at the cost of principal. This condition occurs because of the asymmetric information between management and owner that has no access to the information of the company. Therefore, it is interesting to study the actions of management. This research investigate the effects of compensation, leverage that calculate with debt to total asset, size of company with log total asset, and earnings power with net profit margin as the independent variables against the earnings management as the dependent variable. In measuring the earnings management, researcher used the calculationof modified Jones model. The result shows that NPM variable as the projection of earning power and DTA variable as the proxy leverage has positive effect towards the earning management. While the compensation and company size has no effect towards the earning management.Keywords: compensation, leverage, company size, earnings power